Intake of oral photoprotectors by postmen in Porto Alegre - dos Santos, Karina; Zandavalli, Mônica Cristina Brugalli; Carra Forte, Gabriele; Schneider, Aline Petter (Clinical and Biomedical Research, 2017)
Introduction: Postmen are daily exposed to high levels of solar radiation, and lack of protection can result in many health damages. The present study aimed to identify cutaneous phototypes and evaluate the intake of oral photoprotectors by postmen. Methods: Cross-sectional study, carried out from August 2011 to December 2012 in the city of Porto Alegre, state of Rio Grande do Sul, Brazil. Socioeconomic and behavioral data regarding daily solar exposure were collected through a questionnaire. To evaluate the intake of beta-carotene, lycopene and omega-3, two 24-hour dietary recalls were applied. Cutaneous phototypes were assessed by Fitzpatrick’s classification. Results: A total of 181 postmen were analyzed, whose mean age was 40.2±11.4 years old, and 140 (77.3%) were male. The cutaneous phototypes II, III and IV were the most prevalent (n=138), totaling 76.3% of the sample. The median for the oral photoprotectors intake was 1.16 mg (0.46 – 2.29) of beta-carotene, 3.60 mg (1.01 – 6.31) of lycopene and 0.95 g (0.61 – 1.45) of n-3 fatty acids, all values significantly lower than the minimal doses to obtain photoprotective effect (p<0.001). The individuals in the group of phototypes V and VI showed lower adherence to the use of sunscreen and lower intake of beta-carotene, comparing to the other groups. Conclusions: The intake of oral photoprotectors is low in this population. Future studies may evaluate the real effect of oral photoprotectors, so that preventive measures using this approach can be included in photoprotection education actions for outdoor workers. Keywords: Diet; food and nutrition; skin aging; skin neoplasms; occupational health